2017
DOI: 10.2109/jcersj2.17099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle dispersion on the properties of suspension-sprayed coatings

Abstract: Suspension spraying is a promising surface modification technique, because finer particles can be used in contrast to the case of conventional thermal spraying. However, the optimal conditions for preparing suitable suspensions have not yet been established. Thus, the effects of particle dispersion and flocculation states on the properties of suspension-sprayed coatings were examined in the present study. Y 2 O 3 suspensions were prepared using various quantities of the dispersant. The flow curves and gravitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…It is considered that the particles flocculated and formed gelation structure due to the sedimentation concentration at that point, after maintaining the same dispersion state from the beginning. The same phenomena were confirmed in previous works [11][12][13][16][17][18]…”
Section: Rheological Characteristics Evaluationsupporting
confidence: 90%
See 1 more Smart Citation
“…It is considered that the particles flocculated and formed gelation structure due to the sedimentation concentration at that point, after maintaining the same dispersion state from the beginning. The same phenomena were confirmed in previous works [11][12][13][16][17][18]…”
Section: Rheological Characteristics Evaluationsupporting
confidence: 90%
“…This method can distinguish the difference in sedimentation rate that depends on the particle dispersion state. It has also been used to effectively measure dense slurries directly [11][12][13][14][15][16][17][18]. However, it was not confirmed whether the results are correlated with the green body density.…”
Section: Introductionmentioning
confidence: 96%
“…We have proposed a slurry evaluation technique using a hydrostatic pressure method based on the particle sedimentation phenomena reported in several studies 24–32 . Additionally, in a previous study, this technique was applied to an aqueous dense barium titanate slurry, which demonstrated that the relationship between the measurement result and packing fraction of green sheet had a better correlation than other slurry evaluations 32 .…”
Section: Introductionmentioning
confidence: 99%